Role of malic acid in pycnidiospore germination of Ascochyta rabiei and chickpea blight resistance - C. DEVAKUMAR, P.J. SINGH, MAHENDRA PAL and (Indian Phytopathology, 2002)
Pycnidiospore germination of Ascochyta rabiei, causal agent of chickpea blight, was significantly enhanced in low concentrations of malic acid (0.005 and 0.01%) but it was severely retarded at higher concentrations (1.5 and 2.0%). The total organic acids (of which malic acid is a major component) present in surface washings of leaf and shoot tissues of 12 chickpea lines (BGM 419, GNG 146, L 550, ILC 1929, GL 1014, G 13-1, I-13, G 40, CPI 56566, P 1528-1-1, JM 595 and Galben) was, in general, higher in susceptible than in resistant lines. In contrast, the endogenous level of malic acid, as determined in leaf tissues alone, was higher in the resistant than in the susceptible types. The role of malic acid in chickpea blight resistance is briefly discussed.